(untitled) (Global Journal of Human-Social Science, 2019)
important to note that the narrative took place sometime late in the twentieth century, most likely around the 1980s, the decade when the novel was written. It takes the reader to a place of symbolically woven cultural codes. This paper aims to bring out Jack Gladney’s journey to a postmodern estrangement and shows how we subconsciously become part of his falling self. This novel also unveils the sociopolitical darkness of American society. The ultimate purpose of the paper is to bring into focus the corruption that DeLillo wants us to see in the vision of Jack Gladney’s modernist displacement and postmodernconscience powered by technology, and moral corruption. In the end, the paper will try to unfold Jack Gladney’s internal struggle against his overwhelming fear of death.